Verbs Application Range in Marzbān-Nāmeh (Variety of Meaning, Light Verbs and Arabic Root Nouns Completing the Meaning of the Light Verbs) - Sadeghi Amin, Mahdi (LANGUAGE ART, 2020)
Persian prose is developed in line with poetry in 12th and 13th centuries and reaches its climax. At this time Marzbān-nāmeh which was translated and edited by great writer Sadedin Varavini and has always been welcomed by all the literature fans deserves high consideration in different aspects. Verb has special importance in linguistic examinations because it is the center of gravity and the most important part of sentence and the only element indicating the role-played by other elements. In this study some of the most important verbal functions and most frequent verbs in Marzbān-nāmeh were examined including variety of the verbs' meanings and special functions. The study findings indicate the verbs are used vastly in Marzbān-nāmeh and the writer has benefited from many occasions to neutralize the verbs' monotony and repetition in his work; so he has used many words to have variety of light verbs. The most usable light verb is “To do” in Persian and may be accompanied by different nouns to create a phrasal verb. About 22 percent of Arabic nouns completing the light verbs are with Persian light verbs to create phrasal verbs.